2016
DOI: 10.1177/1363459316674787
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative investigation of lay perspectives of diagnosis and self-management strategies employed by people with progressive multiple sclerosis

Abstract: Abstract:This paper explores how people with progressive Multiple Sclerosis (MS) give meaning to their experiences. It builds upon the self-management literature, which has captured the tension between the desire for retaining normalcy and the increasing burden of self-management associated with chronic disease progression. This repeat interview study is empirically grounded in twenty eight interviews with fourteen people with progressive MS. We identified gender differences in diagnosis-seeking which impacted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…In addition to new knowledge, this study confirmed the earlier findings (Frost et al, 2016; Kang and Ellis-Hill, 2015) that the maintenance of existing lifestyles and physical activities create the feeling of success in the early stages of the disease. Referring to the paradox of quality of life, this study revealed that although implementation of new practices would promote functional well-being, people want to continue with existing lifestyle to maintain dignity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition to new knowledge, this study confirmed the earlier findings (Frost et al, 2016; Kang and Ellis-Hill, 2015) that the maintenance of existing lifestyles and physical activities create the feeling of success in the early stages of the disease. Referring to the paradox of quality of life, this study revealed that although implementation of new practices would promote functional well-being, people want to continue with existing lifestyle to maintain dignity.…”
Section: Discussionsupporting
confidence: 89%
“…In cases like this, Trail et al (2008: 213) have suggested turning to an occupational therapist for evaluation and rehabilitation. However, the usage of these services can link a person more closely with the illness identity when there is actually a need to ensure the maintenance of normality (Frost et al, 2016) and the identity of a healthy person.…”
Section: Resultsmentioning
confidence: 99%
“…To improve the authenticity of the synthesis, 28 research team members with MS read the analyses and contributed personalized reflections, which were translated into I-poem 29 Wrong study focus 19…”
Section: Synthesis With Knowledge Expertsmentioning
confidence: 99%
“…Added to this, many patients will comment that the word 'progression' produces an almost visceral reaction. A sense of the inevitability of neurodegeneration can leave patients feeling hopeless and can increase the risk of treatment non-adherence [21,22]. A more patient-oriented care approach, which looks at symptom management, quality of life, and things that patients can control, can be more motivating than focusing on a negative future [5,23].…”
Section: Risks Of Open Communication About Disease Progressionmentioning
confidence: 99%